STONE CLEARANCE AND COMPLICATION RATE OF MICRO PERCUTANEOUS NEPHROLITHOTOMY AND RETROGRADE INTRARENAL SURGERY FOR LOWER POLE RENAL STONE: A RANDOMIZED TRIAL - Sajjad, Kumail; Maisam Ali Shahid,; Mazhar Ali,; Khizar Hayat,; Muhammad Nazir, (Journal of Ayub Medical College Abbottabad, 2024)
Background: The use of unhealthy food and a sedentary lifestyle increases daily health problems. Renal stones are one among others. Endourology promises the minimum complications and the highest stone clearance rate. Indications of the two procedures overlap micro-PCNL and RIRS. The objective was to evaluate stone clearance and complication rate of micro-PCNL and RIRS for lower pole renal stones. Methods: The research design of this study was a randomized trial and was done after approval of the ethical review committee. The sampling technique was consecutive sampling at the Urology department. Patients included in the study according to inclusion criteria were 96 in number. Randomization into two groups (RIRS vs micro-PCNL) was done by even odd method. All the procedure was done by a single senior urologist. Results: Their ratio among males and females was 2:1. Mean LOS in the RIRS group was 2.89±0.86 days and in the micro-PCNL group 2.58±0.65 days (p=0.047). The complication rate in the RIRS group was 6.2% and 8.3% in micro-PCNL (p=0.695). Mean post-operative haemoglobin was 12.30±1.07 g/dL among the RIRS group and among the micro-PCNL group it was 11.21±1.08 g/dL (p<0.001). There was an average haemoglobin drop in the micro-PCNL group of 1.09±0.01 g/dL. 75% clearance of stone after one session was achieved in the RIRS group while 79.2% was achieved in the micro-PCNL group (p=0.627). Conclusion: Length of hospital stay (LOS) and stone clearance rate (SFR) were similar in both groups with insignificant statistical differences. There is a need to conduct more studies with a large number of study participants and involving multi-centers.